Miłosz o ciele, starości i umieraniu. Nowy język czy dramat (nie)wyrażania? - Pietrych, Krystyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The article discusses Miłosz’s poetic strategies of expression in problems of the body, illness, getting old, and the impending death. Those problems are closely related to Miłosz’s personal experience. The autobiographical plane adds dramatism to Miłosz’s experiments in developing a new poetic language in his old age. Especially in Farther Surroundings seems to develop a new poetical diction in the epistemological sense. The dark tone of the poet is still present, but it gradually weakens and is replaced by words that unambiguously praise (perhaps overpraise) existence, and so reveal their (self)persuasive quality. In this perspective the profusion of texts, which Miłosz wrote in his last years, is evidence of not only of an impressive intellectual power, but also of a drama that was covered by an overload of words.